The Year Round Calendar: An Analysis of Student Outcomes - Kimberly Moore; Deborah A. Verstegen (Educational Considerations, 2004)
Almost a decade ago, the National Education Commission on Time and Learning warned Americans that schools were unable to meet the demands of a new global economy. For 150 years, schools had operated on schedules that suited only the top students, while average and poor students simply dropped out to make decent livings on farms or in factories.